Cyanobacteria-blooming water samples from Lake Taihu induce endoplasmic reticulum stress in liver and kidney of mice - Qin, Wendi (Ecotoxicology (London, England), 2012)
To investigate whether endoplasmic reticulum (ER) stress was involved in apoptosis induced by cyanobacteria-blooming water, healthy male ICR mice were fed with water samples from cyanobacteria-blooming regions of Lake Taihu (China), including Meiliang Bay (M1 and M2), central lake region (H), macrophyte-dominated Xukou Bay (X), and tap water (control group) for three consecutive months. Hepatic and renal mRNA and protein expression of ER stress signaling molecules were measured with quantitative real-time PCR and western blotting. Compared to macrophyte-dominated and control water samples, cyanobacteria-blooming water changed hepatic ER stress signaling molecules. M1 water treatment increased the mRNA and protein levels of glucose regulation protein 78 (GRP78) and C/EBP homologous protein (CHOP), and decreased the mRNA levels of B-cell lymphoma 2 (Bcl-2). M2 water treatment up-regulated GRP78 mRNA and protein expression, whereas H water treatment up-regulated mRNA and protein expression of GRP78 and caspase-12. Cyanobacteria-blooming water exposure also changed mRNA and protein expression of ER stress signaling molecules in the kidneys. M1 water exposure up-regulated GRP78 mRNA and protein expression and CHOP mRNA expression, whereas M2 water treatment up-regulated caspase-12 and Bcl-2 mRNA expression. M1 and M2 cyanobacteria-blooming water exposure significantly increased relative liver weights, and induced hepatic cell apoptosis. However, cyanobacteria-blooming water treatment did not change kidney weights, and did not induce renal apoptosis compared to macrophyte-dominated and control water samples. Hence, cyanobacteria-blooming water induces hepatic apoptosis via ER stress, and ER stress may play an important role in the apparent anti-apoptotic effects on renal cells exposed to cyanobacteria-blooming water